PERFORMANCE OPTIMIZATION OF POLRES PATI KAMSEL UNITS THROUGH DIKMAS LANTAS IN ORDER TO PREVENT TRAFFIC ACCIDENTS - joshua leonard aldriano marbun (Advances in Police Science Research Journal, 2022)
The purpose of this study was to describe the performance of the Pati Police Kamsel Unit and the implementation of Traffic Dikmas activities carried out to prevent traffic accidents in the Pati Police jurisdiction with the hope that the Pati Regency community had awareness and knowledge of driving safety. In writing this final project, the researcher uses several concepts and theories as analytical tools, such as the optimization concept, the traffic education concept, the traffic accident concept, performance theory and management theory. The approach used in this study is qualitative. Techniques Data collection was carried out using observation, interviews, and document studies. The data analysis technique was carried out using data reduction techniques, data presentation and concluding. Based on the results of research that has been carried out that the performance produced by the Kamsel unit through Traffic Dikmas activities to prevent traffic accidents is still far from expectations because the level of awareness of the people of Pati Regency for driving safety is still very low and the implementation of Traffic Dikmas activities carried out by the Pati District Police Kamsel Unit, not by the activity plan that has been made. It can be concluded that in terms of the performance of the Pati Police Kamsel Unit through the Traffic Dikmas to prevent traffic accidents it can still be improved by paying attention to the indicators of quality, quantity, timeliness, effectiveness and independence. As well as in terms of the implementation of the Traffic Education Unit activities carried out by the Pati Polres Kamsel Unit, it is necessary to pay attention to the Planning, Organizing, Actuating and Controlling processes by management theory according to Tery.